2017
DOI: 10.1037/com0000074
|View full text |Cite
|
Sign up to set email alerts
|

Association between lateral bias and personality traits in the domestic dog (Canis familiaris).

Abstract: 15Behavioural laterality reflects the cerebral functional asymmetry. Measures of laterality have been 16 associated with emotional stress, problem-solving and personality in some vertebrate species. Thus 17 far, the association between laterality and personality in the domestic dog has been largely 18 overlooked. In this study we investigated if lateralised (left or right) and ambilateral dogs differed in 19 their behavioural response to a standardised personality test. The dog's preferred paw to hold a 20Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 53 publications
(107 reference statements)
3
21
0
Order By: Relevance
“…Some investigations have found a significant leaning towards right limb use in female dogs and left limb use in males (McGreevy et al, 2010;Quaranta et al, 2004;Wells, 2003). More recent work involving neutered, or a combination of castrated and entire, subjects, however, has typically found no sex differences in dogs' paw use (Barnard et al, 2017;Batt et al, 2008;Branson and Rogers, 2006;Schneider et al, 2012;Wells et al, 2017). This is more in keeping with the results presented here, using a population of mostly (86%) neutered animals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Some investigations have found a significant leaning towards right limb use in female dogs and left limb use in males (McGreevy et al, 2010;Quaranta et al, 2004;Wells, 2003). More recent work involving neutered, or a combination of castrated and entire, subjects, however, has typically found no sex differences in dogs' paw use (Barnard et al, 2017;Batt et al, 2008;Branson and Rogers, 2006;Schneider et al, 2012;Wells et al, 2017). This is more in keeping with the results presented here, using a population of mostly (86%) neutered animals.…”
Section: Discussionsupporting
confidence: 88%
“…Schneider and colleagues (2013), for example, found very limited support for an association between paw preference and personality (assessed using the C-BARQ) in the domestic dog and questioned whether the aggregated subscales served to mask subtle effects. This is certainly a possibility, as Barnard et al (2017) recently found a significant association between paw preference and canine temperament, in this case assessed using a more independent dog personality test. As to whether the C-BARQ masked any subtle effects in the present study is unclear, although seems unlikely given the significantly different behavioural profile of the animals in the two groups (perhaps arising from the deliberate attempt to target animals with therapist-assessed behaviour problems).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several authors have drawn attention to the purported association between motor bias and animal welfare (Barnard et al, 2017;Rogers 2010;Wells et al, 2017), but the findings from this, and other recent studies, raise questions as to which test of paw preference may be the most appropriate to employ to this end. Further work is needed to explore the complex relationship between limb use and brain lateralisation before firm conclusions on the merits of using paw preference as a tool for assessing at-risk individuals can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences will also interact with task demands in determining the degree to which one or both hemispheres are employed to process information and behavioural lateralisation. Laterality has been linked to personality in some species (e.g., fish -Brown and Bibost, 2014;cats -McDowell et al, 2016), including, more recently, dogs (Barnard et al, 2017), with authors finding a strong relationship between traits associated with stronger emotional reactivity (aggressiveness, fearfulness, sociability) and ambilaterality. In a similar vein, Branson and Rogers (2010) found that mixed paw use on the Kong test is associated with an increased fear of thunderstorm sounds in dogs, highlighting the association between emotional functioning and motor output.…”
Section: Discussionmentioning
confidence: 99%